2015
DOI: 10.1016/j.hbrcj.2014.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of circular footing resting on laterally confined granular reinforced soil

Abstract: Three dimensional physical laboratory models were examined to investigate the influence of soil confinement on circular footing behavior resting on granular soil. A total of 23 model footing tests were performed. Nine hollow cylinders with various heights and diameters were installed around the footing model for soil confinement purpose. Square geogrid layers were placed at different depths beneath the bottom edge of the cylinder. Different parameters such as height, diameter, and depth of the cylinder were st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 9 publications
(8 reference statements)
0
6
0
Order By: Relevance
“…Keeping economy in view, confinement technique is one of the suitably applicable methods that have been accepted to enhance the bearing capacity of footing and reduce settlement to permissible limit. In the past few years different materials such as geocell, un-plasticized polyvinyl chloride (Upvc) cylinder, semi flexible vertical reinforcement, mild steel casing, plastic hollow cylinder, timber box have been used as confiner and shown notable improvement in bearing capacity of footing ( Rajgopal et al [25], Sawaaf and Nazer [30], Jha [18], Krishna et al [21], Elsaied [13], Amarasinghe et al [2]). Mandal and Manjunath [23] used geogrid and bamboo sticks as vertical reinforcement elements and studied their effect on the bearing capacity of a strip footing.…”
Section: Introductionmentioning
confidence: 99%
“…Keeping economy in view, confinement technique is one of the suitably applicable methods that have been accepted to enhance the bearing capacity of footing and reduce settlement to permissible limit. In the past few years different materials such as geocell, un-plasticized polyvinyl chloride (Upvc) cylinder, semi flexible vertical reinforcement, mild steel casing, plastic hollow cylinder, timber box have been used as confiner and shown notable improvement in bearing capacity of footing ( Rajgopal et al [25], Sawaaf and Nazer [30], Jha [18], Krishna et al [21], Elsaied [13], Amarasinghe et al [2]). Mandal and Manjunath [23] used geogrid and bamboo sticks as vertical reinforcement elements and studied their effect on the bearing capacity of a strip footing.…”
Section: Introductionmentioning
confidence: 99%
“…El Wakil [14] reported that the bearing capacity of the footing was directly and inversely proportional to the skirt depth and the relative density respectively of the sand. The use of skirts for improving the load-settlement response of circular footing on reinforced sand was explored by Elsaied et al [15]. Based on 23 laboratory small scale model tests, it was concluded placing geogrid layers below the skirted footing improves the bearing capacity up to 7.5 times in comparison to the unconfined case.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, experimental research on skirted footings such as strip [5][6][7], square [4,[8][9][10][11][12], circular [6,[13][14][15][16][17][18][19][20][21][22][23] and rectangular [12], subjected to vertical or inclined loads, has been reported. Numerical studies on skirted footing such as strip [6], square [10] and circular [6] were reported in the literature.…”
Section: Introductionmentioning
confidence: 99%